Consumer Preference Study at a Coffee Shop in Medan Perjuangan District, Medan City Using the Conjoint Method - Hernosa, Siswa Panjang; Akbar, Zainul; Febriyanti Suardi, Tennisya (Jurnal AGRISEP, 2026)
To understand consumer preferences in a more in-depth and structured manner, an analysis method is needed that can identify the product attributes that have the most significant influence on purchasing decisions. The purpose of this study is to identify the characteristics of consumers, attributes, and levels of coffee shops, as well as their locations in Medan Perjuangan District, Medan City. This study uses primary and secondary data. Sampling in this study employed the judgment sampling technique, with a sample of 43 visitors to the coffee shop. The criteria for inclusion were respondents aged 18 years or older who were not students and who had ordered coffee at the coffee shop. The data analysis approach is conjoint analysis. The results of the study showed that the characteristics of the most frequent visitors to the coffee shop were male, aged 21-30 years, self-employed, with an income of IDR 2,100,000–IDR 3,000,000, holding a high school education, unmarried, and with no dependents. Furthermore, the attributes and levels that are most in demand by consumers are Kopi Susu drinks, open spaces, sweetness, and < prices of IDR 15,000 and > IDR 15,000, as well as public facilities. So that in the discussion, the order of highest importance is the attributes of the drink, place, price, taste, and facilities. This indicates that the most important attribute when choosing a coffee shop is the quality of the drink. The suggestion given is an innovation related to the development of types of milk coffee drinks.